Analisis SWOT Dalam Menentukan Strategi Kompetitif Sentra Batik Tulis Al-Barokah - M. Ramdan Efendi; Asisi Asisi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The batik shop "Al-Barokah" is one of the major batik companies in Sumenep, which independently carries out production and marketing activities. As a high-medium scale batik company, “Al-Barokah” has several characteristics which are also internal strengths of the company, including the company's trademark that has been registered and officially in Desperindag, namely “Al-Barokah” which is located in the village of Pakandangan Tengah, Kec. Bluto Kab. Sumenep and using SWOT as a tool to compete and introduce 4P. Thus, the purpose of this study is to determine the strategy and method of Swot in determining the competitive strategy of Sentra Batik Tulis Shop. This type of research is qualitative with the research approach used is normative and sociological. The data sources of this research are primary data and secondary data. The data processing and analysis techniques were carried out using the Milles and Heubermen method with three stages, namely data reduction, data display and conclusion drawing. The research results show that the competitive strategy in the Al-Barokah Batik Tulis Center is more dominant and more specific to the development of the company, so that the 4P strategy is used as the main reference in competition, so that the competitive advantage is more dominant. In addition, the company views competitive strategy as the basis for developing its company. After a SWOT analysis, the business has great opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy (Growth Oriented Strategy). This strategy indicates that the company is strong and able to continue to grow by taking existing opportunities or opportunities to achieve maximum turnover. In this strategy, it can improve the competitiveness of written batik businesses in Pakandangan Tengah Village, Bluto District, Sumenep Regency.